Modernism after Poststructuralism; Or, Does Badiou Save Us from Drowning? - Begam, Richard (Modernism/modernity (Baltimore, Md.), 2021)
The film ends when the hapless tramp wins the lottery, is himself transformed into an upstanding citizen and, after a second tumble into the water, decides to return to his life of penniless wandering. What most interests me about Badiou is his theory of the event as a transformational moment, a break in the temporal sequence that brings about radical change, and I will therefore focus my discussion on his principal work, L'être et l'événement or Being and Event, published in 1988.3 What follows develops three lines of analysis. [...]I examine Badiou's theory of the event and indicate how we might use it to think about modernism and subjectivity not as modes of representation but as vehicles of mathematical performativity.4 Finally, I offer an illustration of how the paradigm of mathematical performativity developed here might be applied in two modernist texts: The world on its own—unaided by the describing activities of human beings—cannot.6 Rorty's claim that truth consists in "making" rather than "finding," Wittgenstein's assertion that truth is a function of a specific "language game," and Derrida's contention that there is nothing outside the text ("il n'y a pas de hors-texte") are all examples of the relativism Badiou seeks to contest.7 By contrast, truth for Badiou is a matter not of construction but of revelation, emerging as the product of an "event" that summons forth a "new way of being," one that fundamentally redefines a subject's "situation," his or her relation to those norms that shape human belief and guide human conduct.8 For Badiou there are four areas in which truth manifests itself, four "generic procedures" to which truth attaches itself (Being and Event, 16).